The PALBONET Trial: A Phase II Study of Palbociclib in Metastatic Grade 1 and 2 Pancreatic Neuroendocrine Tumors (GETNE‐1407). (11th February 2020) - Grande, Enrique; Teulé, Alex; Alonso‐Gordoa, Teresa; Jiménez‐Fonseca, Paula; Benavent, Marta; Capdevila, Jaume; Custodio, Ana; Vera, Ruth; Munarriz, Javier; La Casta, Adelaida; Díez, Juan José; Gajate, Pablo; et al.
Abstract: Lessons Learned: Palbociclib demonstrated no detectable activity in molecularly unselected and heavily pretreated patients with advanced grade 1/2 pancreatic neuroendocrine tumors. Predictive biomarkers that improve patient selection should be investigated in future studies of palbociclib. Background: Palbociclib, a CDK4/6 inhibitor, has shown in vitro activity in pancreatic neuroendocrine tumor (pNET) cell lines. Here we prospectively assessed the activity and safety of palbociclib in monotherapy in metastatic refractory pNETs. Methods: This was a nonrandomized, open‐label, phase II study of patients with metastatic grade (G)1/2 pNETs recruited from 10 centers in Spain. Palbociclib 125 mg was orally administered once daily for 21 of 28 days until disease progression or unacceptable toxicity. Results: Twenty‐one patients were included; 52.4% were men, and median age was 57.4 years (range, 37.4–73.4). Patients had previously received a median of three prior lines of systemic therapy (range, 1–10) for advanced disease (somatostatin analogues, 71.4%; sunitinib, 81.0%; everolimus, 47.6%; chemotherapy, 47.6%). Nineteen patients were evaluated for objective response rate (ORR), with a median follow‐up of 12.4 months (range, 7.53–19.33). No objective and confirmed responses were observed (0%); 11 (57.9%) patients had stable disease, and 6 of them lasted more than 6 months; 8 (42.1%) patients had disease progression as best response. Median progression‐free survival (PFS) was 2.6 months (95% confidence interval [CI], 0–14.4) and median overall survival (OS) was 18.7 months (95% CI, 7.4–29.9; Fig. 1). Most frequent toxicities of any grade were asthenia (76.2%), neutropenia (42.9%), diarrhea (33.3%), and nausea (33.3%). Five (23.8%) patients developed G3–4 neutropenia and two (9.5%) patients developed G3–4 thrombocytopenia. Conclusion: Lack of activity was observed with palbociclib as a single agent in molecularly unselected and heavily pretreated patients with advanced G1/2 pNETs.